A simple non-parametric method for resolving merged doublet lines: insights into complex kinematics and outflows. Issue 3 (14th September 2018) - Villforth, Carolin; Underwood, Tom L; Tolson, Mark; Modha, Nikhil
ABSTRACT: Doublet line emission and absorption are common in astronomical sources (e.g. [O iii ], [O ii ], NaD, Mg ii ). In many cases, complex kinematics in the emitting source can cause the doublet lines to merge, making characterization of the source kinematics challenging. Here, we present a non-parametric method for resolving merged doublet lines when the line ratio and wavelength difference are known. The method takes as input only the line ratio and wavelength difference, using these quantities to resolve the components of the doublet without resorting to fitting (e.g. using multiple Gaussians) or making any assumptions about the components' line profiles (save that they are the same for both components). The method is simple, fast, and robust. It is also ideal for visualization. We show that the method recovers line profiles of merged emission lines in simulated data. We also show, using simulated data and mathematical analysis, that the method does not significantly increase noise levels in the extracted lines, and is robust to background contamination. We demonstrate the strength of the method by applying it to strongly merged [O iii ] 5007/4959 Å in Active Galactic Nuclei. A python implementation of the method is provided in the appendix.